Promoting Autonomy and Employment of Individuals with Intellectual Disability: The Role of Universities - Morcillo, Juana; Bornman, Juan (INKLUSI, 2024)
A positive correlation exists between having a university degree and being employed. The opportunity to earn a university degree, however, is challenging for students with intellectual disability, as universities are typically not adapted to their unique higher education needs. This negatively impacts those students’ employment opportunities and, consequently, also their autonomy because employment is often a driver of important life decisions. In response, the University of Castilla-La Mancha in Spain embarked on a program, ‘Incluye e Inserta UCLM’ (‘Inclusion and Labour Insertion at UCLM’), to accommodate students with intellectual disabilities by implementing an accessible university qualification for them. Universities are knowledge-generating centers and should also fulfill a social function. To do so, universities must be in contact with society to determine societal needs and provide some solutions. The abovementioned socially responsive university program offers students with intellectual disabilities a unique opportunity to fulfill their academic and personal growth. Seseorang yang bergelar sarjana memiliki korelasi positif dengan bagaimana ia dipekerjakan. Namun, kesempatan untuk memperoleh gelar sarjana merupakan tantangan bagi mahasiswa penyandang disabilitas intelektual, karena universitas biasanya tidak disesuaikan dengan kebutuhan unik pendidikan tinggi mereka. Hal ini berdampak negatif terhadap kesempatan kerja bagi penyadang disabilitas intelektual dan juga otonomi mereka, karena pekerjaan seringkali merupakan pendorong keputusan hidup yang penting. Universitas Castilla-La Mancha di Spanyol memulai program 'Incluye e Inserta UCLM' ('Inklusi dan Penyisipan Tenaga Kerja di UCLM') untuk mengakomodasi mahasiswa penyandang disabilitas intelektual melalui penerapan kualifikasi universitas yang dapat diakses oleh mereka. Universitas adalah pusat penghasil pengetahuan dan juga harus memenuhi fungsi sosial. Oleh karena itu, universitas harus berhubungan dengan masyarakat dalam menentukan kebutuhan masyarakat dan memberikan solusi masalah sosial. Program universitas yang tanggap secara sosial ini menawarkan kepada mahasiswa penyandang disabilitas intelektual kesempatan unik untuk memenuhi pertumbuhan akademik dan pribadi mereka.